Search for large extra dimensions in the monojet + ET channel with the DØ detector - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alton, A; Alves, G; et al. (2003)
The article discussed about the large extra dimensions in the monojet channel. The confidence-level lower limits, imposed on the fundamental Planck scale between 0.6 and 1.0 TeV, was 95%. The lower limits were found to be depended on the number of extra dimensions. The resultant limits were complimentary to those obtained in the single photon channel.